2014
DOI: 10.3389/fbioe.2014.00048
|View full text |Cite
|
Sign up to set email alerts
|

Protein Network Signatures Associated with Exogenous Biofuels Treatments in Cyanobacterium Synechocystis sp. PCC 6803

Abstract: Although recognized as a promising microbial cell factory for producing biofuels, current productivity in cyanobacterial systems is low. To make the processes economically feasible, one of the hurdles, which need to be overcome is the low tolerance of hosts to toxic biofuels. Meanwhile, little information is available regarding the cellular responses to biofuels stress in cyanobacteria, which makes it challenging for tolerance engineering. Using large proteomic datasets of Synechocystis under various biofuels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…According to our previously weighted gene co-expression network analysis (WGCNA) with the Synechocystis proteomic data [ 48 ], photosynthesis antenna proteins, porphyrin and chlorophyll metabolism and photosynthesis were identified as the top three significant biofuel-specific responsive pathways after cells were treated with exogenous biofuels [ 48 ]. Therefore, considering the association of responsive sRNA with these three pathways (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our previously weighted gene co-expression network analysis (WGCNA) with the Synechocystis proteomic data [ 48 ], photosynthesis antenna proteins, porphyrin and chlorophyll metabolism and photosynthesis were identified as the top three significant biofuel-specific responsive pathways after cells were treated with exogenous biofuels [ 48 ]. Therefore, considering the association of responsive sRNA with these three pathways (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The genetic locations of nc33 , nc65 , and nc85 sRNA genes are provided in Table 1 . Interestingly, target enrichment analysis showed that Nc65 and Nc85 were enriched in porphyrin and chlorophyll metabolism and Nc33 in photosynthesis; both metabolic pathways were identified as biofuel-specific responsive pathways in our previous study [ 48 ]. This was consistent with a previous study that showed that proteins related to photosynthesis and chlorophyll concentration were up-regulated upon ethanol exposure in Synechocystis cells [ 23 ], indicating that the responses of sRNAs and protein to biofuels could point to similar mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results allow us to set new tasks for the upcoming research of the molecular mechanisms of action of ketones on bacterial cells. [47,48]).…”
Section: Discussionmentioning
confidence: 99%
“… Modes of 2-nonanone action on cyanobacteria cell, (some figure elements are adapted from [ 47 , 48 ]). …”
Section: Figurementioning
confidence: 99%
“…The procedure to construct co-expression network includes:i) data normalization was performed with the raw proteomic or transcriptomic data converted into a ratio of condition versus its control, and then log2 transformed; ii) correlation values were calculated for all possible pairs, in which correlation was defined as the Pearson correlation coefficient for all pairwise genes/proteins; iii) normalized the correlation coefficient using a Min-Max linear normalization algorithm developed previously (Guo et al, 2012), and then the co-expression network was constructed in which the weight of edge represents Pearson correlation coefficients, and the node of network represents genes/proteins (Pei et al, 2014); iv) a correlation coefficient cutoff was applied to the coexpression network, where only gene/protein pairs with a correlation coefficient higher than the cutoff were considered connected. As the biological networks behave like a scale-free network (Tsoi et al, 2014), the distribution of connections follows power-law relationship.…”
Section: Construction Of Bi-colored Networkmentioning
confidence: 99%